Characterizing High-Energy Solar Proton Events with Energies Below and Above 100 MeV - Ameri, Dheyaa; Valtonen, Eino; Al-Sawad, Amjad; Vainio, Rami (Springer Science and Business Media B.V., 2025)
We analyzed 58 high-energy proton events that occurred during the years 1996 – 2022. In 32 out of the 58 (55%) events, the proton energies extended up to ∼68 MeV but did not reach 100 MeV. In the remaining 26 events, the proton energies exceeded 100 MeV. We studied the differences in the characteristics of these proton events and their associations with solar and interplanetary phenomena to improve understanding proton sources and acceleration processes. The coronal mass ejections (CMEs) associated with >100 MeV proton events appeared to be, on average, more energetic than those associated with <100 MeV proton events. The peak and integrated fluxes (fluence) of the soft X-ray (SXR) flares were higher in > 100 MeV proton events, but there was almost no difference in the rise times of the flares. In a major part of the >100 MeV proton events, protons were released over the rise phase of the SXR flares, whereas in most of the <100 MeV events the proton releases occurred after the peak of the SXR flares. We established limits for the CME speed VCME and SXR peak flux Fpk or total fluence Fi, which helped us to distinguish the events in the two groups. Solar eruptions with VCME>1000 km s−1 and F>pk5⋅10−5 W m−2 had a high probability to produce proton events of >100 MeV. On the other hand, eruptions with V>CME900 km s−1 and F100 MeV events. Our analysis showed that protons in most of the >100 MeV events were released low in the corona (≤3.0 R⊙) before the onsets of the DH-Type II radio bursts. Conversely, protons in most of the <100 MeV events were released higher in the corona (>3 R⊙) and after the DH-Type II onsets. We conclude that protons in most of the >100 MeV events are accelerated either by the flare reconnection processes or by shocks low in the corona and could undergo reacceleration higher in the corona in CME shocks manifested in DH-Type II radio emission. In the <100 MeV events, protons are mainly accelerated in CME shocks at coronal heights >3 R⊙.